A comparative assessment of land management approaches in Bhutan. Issue 2 (17th February 2018) - Yeshey,; Shrestha, Rajendra P.; Schmidt-Vogt, Dietrich; Qasim, Said
ABSTRACT: Arable land in Bhutan is under serious threats of land degradation. Proper land management approach is needed to control soil erosion problems. This study is an attempt to characterize and document the conventional and the community-based land management approaches, applied in Chukha and Dagana districts, respectively. The study tried to make a comparative assessment of their social, economic and environmental impacts on the participating farmers. Farmers' level of participation in the program, implementation of the soil erosion control measures (SECM) and subsequent social, economic and environmental impacts were found to be significantly influenced by the type of approach applied. The study found that community-based approach is by any means better suited for the study sites than the conventional approach. The social, economic and environmental attributes of respondents from the community-based approach were found to have improved significantly as compared to the conventional approach. The community-based approach was thus found to have a higher potential to meet the diverse requirements of rural subsistence farming communities in Bhutan than the conventional approach.